ANALYSIS OF THE EXISTING ASPECTS OF THE PROBLEM OF PROCESSING AND USE OF VEHICLE TIRES - Xaliljonov Dostonjon Davronzoda; Abdulatif Abdubannopov (American Journals Publishing, 2023)
In this article, we summarized the problem of car tire recycling, found the need to systematize the existing experience in evaluating the effectiveness of project solutions, justify the social effectiveness of the project. For this purpose, the construction of tire recycling plants plays an important role.
Keywords: Car, quality, specification, production, service, operation.